The effect of extender, age, and bovine sexual status on the sperm kinematics - Araya-Zúñiga, Ignacio (2023)
Introduction. The kinematic patterns of semen are influenced by individual variation and/or environmental effects, determined by the handling after sample collection. Objective. To evaluate the effect of two commercial extenders, bull age, and sexual status on the motility and kinetics parameters of fresh bovine semen. Materials and methods. The study was conducted on the livestock farms “La Vega,” San Carlos, and “La Balsa”, San Ramón, Costa Rica, between March and August 2021. Donated semen from thirteen Brahman bulls was used, extracted through electroejaculation. A total of 45 ejaculates were collected, with a minimum of two and a maximum of five per animal. The semen was diluted with two commercial extenders, Optixcell® and Bioxcell®, at a temperature of 37 °C. The samples were analyzed using the Computer-Assisted Semen Analysis (CASA)-Mot ISAS®v1 system and a reusable Spermtrack® counting chamber (20 μm). Results. Differences (p<0.05) were observed in sperm motility and kinematics, as well as sperm kinetic parameters, depending to the extender used. Bioxcell® showed higher progressive motility (64.03±2.01 %) compared to Optixcell®. Ejaculates diluted with Bioxcell® exhibited a more linear and progressive kinematic pattern than those diluted with Optixcell®, which had lower average velocity (VAP=106.67±0.24 μm s-1) and straightness index (STR=79.35±0.10%). Age did not show differences in total motility, but progressive motility was higher in animals >48 months (62.27±1.87 %). An effect of sexual status was observed with higher linearity, velocity, and sperm oscillation during mating compared to sexual rest. Conclusion. Age, sexual status, and the extender used for semen preservation influenced the sperm quality of bovine ejaculates.